PENINGKATAN MINAT BELAJAR SISWA SEKOLAH DASAR SELAMA PANDEMI COVID-19 DI DESA ROWOTAMTU KABUPATEN JEMBER - Afkarina, Izza (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
Rowotamtu is one of the villages which is affected by the Covid-19 pandemic. The village has more than 3 elementary and private primary schools with high educational activities. During the Covid-19 pandemic, elementary school students in this village experienced various problems in online learning. Therefore, this KKN program aims to increase the learning interest, knowledge, and creativity of students during the Covid-19 pandemic. The methods of this program are observation, implementation, and evaluation. The learning innovation programs that have been created are environmental learning, simple science experiments, and handicraft art. The evaluation of the learning is conducted by using pretests and posttest questionnaire to measure the students understanding and learning interest quantitatively. The result of this program shows that the learning Innovation in the teaching program is successfully increasing student’s learning interest, knowledge, and creativity